2012
DOI: 10.1118/1.4754654
|View full text |Cite
|
Sign up to set email alerts
|

Cupping artifact correction and automated classification for high‐resolution dedicated breast CT images

Abstract: A cupping artifact correction method and an automatic classification method were applied and evaluated for high-resolution dedicated breast CT images. Breast tissue classification can provide quantitative measurements regarding breast composition, density, and tissue distribution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 56 publications
3
49
0
Order By: Relevance
“…We had observed that cupping artifacts can be corrected by using reconstructed image. Similar observations had also been reported in the literature 19 , 20 …”
Section: Introductionsupporting
confidence: 92%
See 3 more Smart Citations
“…We had observed that cupping artifacts can be corrected by using reconstructed image. Similar observations had also been reported in the literature 19 , 20 …”
Section: Introductionsupporting
confidence: 92%
“…We find another cupping artifact method inspired by the MR bias correction method from the work by Yang et al (19) The results are shown in Fig. 8.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several other authors have developed bCT segmentation algorithms. Notable among them are Chen, 29 Nelson et al, 30 and Yang et al 31 Chen used histogram partitioning into five subintervals followed by interval thresholding to decompose the breast into five segmentation classes based on voxel intensity. The methods of Nelson et al employed a two compartment histogram model to classify adipose, glandular, and skin tissues.…”
mentioning
confidence: 99%